A confusion of princes - Nix, Garth (New York : Harper, 2012)
"Battling aliens, space pirates, and competitors, Prince Khemri meets a young woman, named Raine, and learns more than he expected about the hidden workings of a vast, intergalactic Empire, and about himself"--Provided by publisher.
Keywords: Science fiction; Princes -- Fiction; Adventure and adventurers -- Fiction; Inheritance and succession -- Fiction